Developing the Competence of the Class Head to Work in A Team of Students in Continuous Professional Development - Nurmanova Dilfuza Jamilovna (Zien Journals, 2023)
In the continuous professional development system, in order to increase the competence of class leaders to work with the class team, practical methodical recommendations are given to class leaders by organizing short-term courses in the process of continuous professional development
Keywords: Class leader; class team; student